Diffuse scarring alopecia in a female pattern hair loss distribution. (17th February 2017) - Fergie, Bonnie; Khaira, Gurpreet; Howard, Vicki; de Zwaan, Sally
Abstract: We describe three cases of hair loss in a female pattern hair loss (FPHL) distribution with histologic features of lichen planopilaris (LPP). All patients had a history of diffuse, gradual hair loss in a Christmas tree pattern that clinically presented as FPHL on gross and dermoscopic examination. Notably, there were no characteristic clinical signs of LPP and no histologic features of FPHL. These cases are most consistent with cicatricial pattern hair loss (CPHL). This relatively new entity is similar to fibrosing alopecia in a pattern distribution (FAPD) in that they are both scarring alopecias confined to a FPHL distribution, but CPHL lacks the clinical signs of perifollicular erythema and perifollicular keratosis seen in FAPD. These three cases may present an early, subtle form of CPHL and will be of interest to clinicians and histopathologists alike.